2020
DOI: 10.3390/molecules25102426
|View full text |Cite
|
Sign up to set email alerts
|

Polish Propolis—Chemical Composition and Biological Effects in Tongue Cancer Cells and Macrophages

Abstract: The purpose of this study was to compare the chemical composition and biological properties of Polish propolis. Ethanol, ethanol-hexane, hexane and hexane-ethanol extracts of propolis from three different regions of Poland were prepared. On the basis of the evaluation of their chemical composition as well as the extraction yield and free radical scavenging activity, the ethanol and hexane-ethanol extractions were proposed as the most effective methods. Subsequently, the biological properties of the extracts we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…In Algerian black poplar buds, the total amount of flavonoids in ethanolic extract reaches about 13.65 mg quercetin eq/g [32], and researchers found that Polish propolis has a total flavonoid content of 18.76 mg quercetin eq/g [33]. In Lithuanian black poplar buds' extract, we found higher amounts of flavonoids compared to Algerian researchers, around 24.76 mg rutin eq/g, and similar amounts of flavonoids in propolis extract compared to Polish propolis extract [32,33]. Other authors found similar amounts of flavonoids in black poplar buds [34], but no data were found on the total amount of flavonoids in balsamic poplar buds.…”
Section: Discussionmentioning
confidence: 99%
“…In Algerian black poplar buds, the total amount of flavonoids in ethanolic extract reaches about 13.65 mg quercetin eq/g [32], and researchers found that Polish propolis has a total flavonoid content of 18.76 mg quercetin eq/g [33]. In Lithuanian black poplar buds' extract, we found higher amounts of flavonoids compared to Algerian researchers, around 24.76 mg rutin eq/g, and similar amounts of flavonoids in propolis extract compared to Polish propolis extract [32,33]. Other authors found similar amounts of flavonoids in black poplar buds [34], but no data were found on the total amount of flavonoids in balsamic poplar buds.…”
Section: Discussionmentioning
confidence: 99%
“…Affects cell viability and cellular proliferation; presents cancer-selective antiproliferative activity. [162] Portugal (Northeast and Centre)…”
Section: Propolis Administeredmentioning
confidence: 99%
“…[172] In Europe, research has also been undertaken on the antitumor effects of propolis. In 2020, Wezgowiec and collaborators reported that propolis from Poland possesses antitumor activity against tongue cancer cells (human squamous cell carcinoma derived from tongue, SCC-25), at concentrations of 100, 500, and 1000 µg/mL, affecting cell viability and cellular proliferation after 24 h incubation, but does not have an effect on gingival fibroblasts, indicating the potential of Polish propolis as a natural product with cancer-selective antiproliferative activity [162]. Similarly, research has examined the antitumor effect of propolis from northeastern and central Portugal (0-100 µg/mL) on normal and cancerous renal cells derived from human renal cell carcinoma patients, and in the A-498 (Human renal epithelial cancer) cell line.…”
Section: Propolis Administeredmentioning
confidence: 99%
“…Over the past few years, the biological activities of Polish propolis were studied intensively, and its chemopreventive, antioxidant, antibacterial, antiproliferative, and antifungal activity was observed [ 4 , 5 , 8 , 9 , 30 , 31 , 32 , 33 ]. Moreover, propolis collected from an apiary located in the central–western part of Poland effectively protected human red blood cells (RBC) in vitro against 2,2′-azobis(2-methylpropionamidine) dihydrochloride (AAPH)-induced oxidative hemolysis [ 19 , 34 ].…”
Section: Introductionmentioning
confidence: 99%